Assessment of Self-Care Practices Among Hypertensive Patients at Meru Teaching and Referral Hospital, Kenya. - Kathuri, Elizabeth; Gichunge, Catherine; Kathuri, Elizabeth Wandia (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Background: Globally hypertension has been on the rise among the adult population with countries in sub-Saharan Africa (SSA) carrying the highest burden. Self-care practices have been proven to improve the risk factors and reduce severity of hypertension. The aim of this study was to investigate the adherence of self-care practices among hypertensive patients at the Meru Teaching and Referral Hospital. Methods: A cross-sectional survey was conducted among 75 hypertensive patients attending the Medical Outpatient Clinic at the Meru Teaching and Referral Hospital. Data was analyzed using descriptive statistics and inferential statistics. Results: The average mean age of the participants was 58.53 years and the majority were females (n=39, 52%). Of the participants who had consumed alcohol before hypertension diagnosis (26.7%, n=20), a quarter of them (25%, n= 5) had used alcohol in the last one month prior to the study. A small percentage (9.33%, n=7) of the participants reported to be currently smoking. Majority of the participants, 93.3% (n= 70) used liquid vegetable oil for cooking. More than half of the participants (64%, n= 48) reported that they added raw salt to their food. Only 40% (n=30) of the participants consumed fruits daily. This varied with vegetable intake where majority of the participants (69.3%, n=52) reported daily intake. Almost all of the participants 98.7% (74) consumed less than 5 servings of fruits and vegetables in a day, with a mean serving of 1.41(±0.90). Majority of the participants (85.4%, n=64) performed moderate to vigorous activity. Conclusions: Of the six self-practices that were assessed among hypertensive patients, two were not well adhered to by the majority of the participants. Recommendations: Health care workers to continuously educate the patients on self-care strategies that will help improve adherence of all the recommended self-care practices.